2018
DOI: 10.1016/j.jvs.2018.05.206
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular delivery of resolvin D1 inhibits neointimal hyperplasia in a rabbit vein graft model

Abstract: Objective: Inflammation is a key driver of excessive neointimal hyperplasia within vein grafts. Recent work demonstrates that specialized proresolving lipid mediators biosynthesized from omega-3 polyunsaturated fatty acids, such as resolvin D1 (RvD1), actively orchestrate the process of inflammation resolution. We investigated the effects of local perivascular delivery of RvD1 in a rabbit vein graft model. Methods: Ipsilateral jugular veins were implanted as carotid interposition grafts through an anastomoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…Omega-3 fatty acids decrease inflammation ( Serhan, 2014 ), and inhibit intimal hyperplasia in mice ( Li et al, 2015 ). Other studies have shown similar effects after administration of the pro-resolving lipid mediators resolvins and maresins, which are enzymatically formed from omega-3 fatty acids ( Ho et al, 2010 ; Akagi et al, 2015 ; Liu et al, 2018 ; Wu et al, 2018 ). The latter studies provided the initial evidence that stimulating the resolution of inflammation by means of lipid pro-resolving mediators would promote an adequate healing of vascular injury.…”
Section: Introductionmentioning
confidence: 64%
“…Omega-3 fatty acids decrease inflammation ( Serhan, 2014 ), and inhibit intimal hyperplasia in mice ( Li et al, 2015 ). Other studies have shown similar effects after administration of the pro-resolving lipid mediators resolvins and maresins, which are enzymatically formed from omega-3 fatty acids ( Ho et al, 2010 ; Akagi et al, 2015 ; Liu et al, 2018 ; Wu et al, 2018 ). The latter studies provided the initial evidence that stimulating the resolution of inflammation by means of lipid pro-resolving mediators would promote an adequate healing of vascular injury.…”
Section: Introductionmentioning
confidence: 64%
“…Adapted with permission from ref. 48 ship between changes in the O3I and these SPM pathway markers (109). However, downstream bioactive SPMs were sparsely detected in plasma, and measures of endothelial function and systemic inflammation were unchanged following the 1-month intervention.…”
Section: Translation: Developing a Platform For Pro-resolving Vasculamentioning
confidence: 98%
“…Based on the findings from smallanimal models described above, we have sought to develop a platform for pro-resolving vascular therapeutics leveraging polymer and device technologies ( Figure 2). Using poly(lactic-co-glycolic acid) (PLGA) as a biodegradable scaffold, we described thin-film devices capable of directional elution of bioactive RvD1 over several weeks (47,48,96). Others have described similar approaches using biomaterial scaffolds to locally deliver SPMs to subcutaneous tissues (97,98) and bone (99).…”
Section: Translation: Developing a Platform For Pro-resolving Vasculamentioning
confidence: 99%
See 1 more Smart Citation
“…Weber et al 17 report a new bacterial nanocellulose-derived vascular graft in a sheep model, another step toward developing better grafts. Wu et al 18 show that resolvin D1 promotes resolution of inflammation and inhibits neointimal hyperplasia. And, Braetz et al 19 show that sphingosine-1-phosphate receptor-1 regulates neointimal hyperplasia and may be another good pharmacological target.…”
mentioning
confidence: 99%